Calculation Of the Heating System for Cassava Pulp Dryer Using Rotary Dryer with Capacity Of 5 kg/hour - Mardiah, Enok; Pranoto, Hadi (International Journal of Advanced Technology in Mechanical, Mechatronics and Materials, 2025)
Drying cassava pulp is an important stage in the cassava processing process so that the final product has good quality and high shelf life. This research aims to design and calculate the heating system in a cassava pulp drying machine based on a rotary dryer with a capacity of 5 kg/hour. The methods used include preliminary studies and field observations, literature review, and technical calculations including air flow velocity, moisture content, heat required, drying efficiency, and fuel requirements. The calculation results show that the total heat energy required to reduce the water content of cassava pulp from 20% to 5% is 2176.73 kJ, while the heat provided by the heating air is 4493.88 kJ with a thermal efficiency of 48.44%. The fuel used is LPG with a requirement of approximately 50 grams per drying cycle. The system shows potential as an effective alternative to traditional drying methods, especially for household or micro-enterprise scale. Further optimisation is required to improve the thermal efficiency and heat distribution.